Adaptability and yield of a new cultivar of spring barley Yarushnik - I. N. Shchennikova; L. P. Kokina; I. Yu. Zaytseva; L. V. Panikhina (Аграрная наука Евро-Северо-Востока, 2024)
The research was carried out in the conditions of the Kirov region. The purpose of the study of 2021…2023 was to evaluate the biological and economic properties of a new cultivar of spring barley ʽYarushnik’, transferred to the state variety testing in 2024. Field research was conducted in a competitive test according to the Methodology of the state variety testing of agricultural crops. The comparison was carried out with ʽRodnik Prikamiya’ standard and the cultivars ‘Pamyati Rodinoy’ (2014) and ʽBoyarin’ (2023) previously included in the State Register. To assess the yield in different growing years and the adaptive abilities of cultivars, the methods described in the works of I. N. Voronchikhina and co-authors (2002), A. A. Goncharenko (2005) and A. V. Kilchevsky (2005) were used. The cultivar was created by the method of intraspecific stepwise hybridization with double selection. The balance in a hybrid combination of high-yielding collection samples Sv 88764 (Sweden) and Annabel (Germany) with the cultivar ‘Duet’ (bred by the Federal Agricultural Research Center of the North-East, Russia) became the basis for the creation of a high-yielding, resistant to region-specific environmental stress factors of the spring barley cultivar ‘Yarushnik’. The new cultivar is mid-ripening, with a high and stable yield over the years (6.21 t /ha), forms a large grain with good technological properties: nature – 705 g/l, protein content in the grain – 13.0 %, grain yield – 55 %. In terms of grain quality, it is a cultivar of grain-forage use. The reaction of the studied barley varieties to environmental conditions was revealed. Comparison with the standard cultivar ‘Rodnik Prikamiya’ revealed the advantage of the new variety in terms of overall adaptive ability (ОАСi = 0.37, standard – -0.41), relative stability of the genotype (Sgi = 35.62; standard – 45.16), breeding value of the genotype (СЦГi = 3.08; standard – 1.76). According to the complex index, the clear superiority of the ‘Yarushnik’ cultivar (1.09) over the standard (0.74) was also revealed.